A new species of Rhadinella (Serpentes: Colubridae) from the Pacific versant of Oaxaca, Mexico - Campbell, Jonathan A. (Zootaxa, 2015)
I describe a new species of Rhadinella from the Pacific versant of Oaxaca, Mexico, a region where the genus was previously unknown. This diminutive snake is a member of a group of snakes that have dark dorsal coloration, which mostly or completely obfuscates a pattern of longitudinal striping characteristic of most species of Rhadinella. The closest relative of the new species, on the basis of morphological similarities, appears to be Rhadinella pilonaorum which occurs to the east of the Isthmus of Tehuantepec about 800 km from the type-locality of the new species.